Mechanical criterion for coal and gas outburst: a perspective from multiphysics coupling - Liu, Ting; Lin, Baiquan; Fu, Xuehai; Liu, Ang (International journal of coal science & technology, 2021)
Although a series of hypotheses have been proposed, the mechanism underlying coal and gas outburst remains unclear. Given the low-index outbursts encountered in mining practice, we attempt to explore this mechanism using a multiphysics coupling model considering the effects of coal strength and gas mass transfer on failure. Based on force analysis of coal ahead of the heading face, a risk identification index C m and a critical criterion ( C m ≥ 1) of coal instability are proposed. According to this criterion, the driving force of an outburst consists of stress and gas pressure gradients along the heading direction of the roadway, whereas resistance depends on the shear and tensile strengths of the coal. The results show that outburst risk decreases slightly, followed by a rapid increase, with increasing vertical stress, whereas it decreases with increasing coal strength and increases with gas pressure monotonically. Using the response surface method, a coupled multi-factor model for the risk identification index is developed. The results indicate strong interactions among the controlling factors. Moreover, the critical values of the factors corresponding to outburst change depending on the environment of the coal seams, rather than being constants. As the buried depth of a coal seam increases, the critical values of gas pressure and coal strength decrease slightly, followed by a rapid increase. According to its controlling factors, outburst can be divided into stress-dominated, coal-strength-dominated, gas-pressure-dominated, and multi-factor compound types. Based on this classification, a classified control method is proposed to enable more targeted outburst prevention.